Perancangan User Experience Aplikasi Pemantau Kesehatan pada Lansia menggunakan Metode Human-Centered Design - Saarah Dina Wahyuningtyas; Lutfi Fanani; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The eldelry is a person aged 60 years or older (Republik Indonesia, 1998). They have different body conditions from adult humans in general. As stated in (Kementerian Kesehatan RI, 2013), the complications are usually suffered by the eldelry are hypertension, stroke, diabetes, arthritis or rheumatism. The tardiness of treatment conduces in other system disruption and decreases daily activities (Naryani P & Kartinah, 2009). Therefore, a great family role is required so that the elderly can spend the rest of their lives greatly and increase their life expectancy. The use of elderly health monitoring application can assist the family in providing health services. This study aimed to design a user experience on the elderly health monitoring application, so it is expected to provide comfort. The method used to design the user experience of the application is Human-Centered Design, while the evaluation used a heuristic evaluation involving 4 assessors. In this study, the evaluation of the solution design went through 2 stages, the first evaluation stage was finding problems, then the second stage was a consolidation process to discuss the answers obtained from each evaluator into a single unit. The evaluation results obtained 22 problems, where these problems will be repaired based on the highest to the lowest severity ratings.